PENGARUH LATIHAN DROPSHOT MENGGUNAKAN RINTANGAN TALI 0,5 METER TERHADAP KEMAMPUAN PUKULAN FOREHAND OVERHEAD DROP DALAM PERMAINAN BULUTANGKIS PADA CLUB PB. BERSAMA MASBAGIK TAHUN 2015 - Lalu Sapta Wijaya Kusuma (Universitas Pendidikan Mandalika, 2017)
Weak technique in doing dropshoot punch, a lot of players do the punch is less than the maximum, because there are still many dropshot blows that fall far near the net, so that the punch can still be taken by the opponent players. Dropshoot blows both forehand and backhand basically the same, because it is done with the same motion techniques, but the difference is the location of the ball so only a lot of players who are still not maximized when doing dropshoot blows, especially backhand overhead drop punch. The formulation of problem in this research is; Is there any effect of the drop shot exercise using a 0.5 meter rope barrier against the ability of backhand overhead drop punch in badminton at Club Badminton Association with Masbagik East Lombok 2015? The general objective in this research is to know whether or not the effect of drop shot exercise using a 0.5 meter rope against the backhand capability of overhead drop in badminton game. The design of this research is one group pre-test and post-test design. The sample in this study amounted to 15 people from Club PB. Bersama. The formula used in this study is t-test with the results of the research note that the t-count for backhand backhand overhead drop of 2.269, and t-table of 2.145, or in other words (2.269> 2.145). So it can be drawn a conclusion that: there is the effect of dropshoot exercise using 0.5 meter rope barrier to the ability of backhand overhead drop punch in badminton game at Badminton Bersama Masbagik Club Lombok Timur 2015